Ayurvedic Insights into Recurrent Abortions: A Comprehensive Literature Review - Samiksha Rawat; Pravesh Tomar (AYUSHDHARA, 2025)
Recurrent pregnancy loss affects around 15% of pregnancies globally. Ayurveda provides a comprehensive method for comprehending and treating this problem through concepts like Garbhotpatti (conception) and Garbhasrava (miscarriage). This study reviews classical Ayurvedic literature with a focus on pathophysiology, etiology, and treatment approaches. key components include Garbhadhana Yogya Ayu, Garbhasambhava Samagri, Garbhadhana Vidhi, Garbhavakranti, Shadbhavas of Garbha, Garbha Poshana and Vriddhi. Causes of recurrent abortions can stem from abnormalities at the time of conception, including factors such as age, and the essential elements of conception: Ritu, Kshetra, Ambu, and Beeja. Even after conception several Garbhoupghatkara Bhavas, alongside causes of Yoni Vyapada, Jataharini, Bandhya and the concept of Douhridaapamana, also contribute to miscarriages. Symptoms often include pain-resulting from the vitiation of Vata-and bleeding, indicative of the expulsion of Ama Garbha and the opening of Artava Vaha Srotas. Ayurvedic classics elucidate various conditions leading to abortions, drawing somehow a conceptual meaning with modern scientific understanding. The concept of Garbhasrava in these texts provides valuable insights in the management of such disorders, emphasizing the need for a holistic approach to women health. Understanding these perspectives can enhance our approach to address recurrent abortions and support women through their pregnancy journeys.